Patterns of agricultural production among male and female holders: Evidence from agricultural sample surveys in Ethiopia - Kasa, Leulsegged; Abate, Gashaw T.; Warner, James; Kieran, Caitlin (International Food Policy Research Institute, 2015)
Gender inequities present a major barrier to increased agricultural production and food security in Ethiopia. However, a lack of nationally representative sex-disaggregated data and analysis hinder the development and implementation of evidence-based policies. This report aims to contribute to filling this gap by presenting a gender analysis of the Ethiopian Central Statistics Agency’s Agricultural Sample Survey (AgSS) data, collected between 2010 and 2013. The analysis reveals clear gender gaps between male and female holders in terms of human capital, natural capital, financial capital, agricultural input use, and participation in crop production and livestock husbandry. Specifically, female holders are less educated, have less family labor, own and manage less land, and are less likely to cultivate rented land compared to male holders. Concurrently, female holders have limited access to extension and advisory services and, therefore, to knowledge and information concerning best agronomic practices. Compared to male holders, female holders are less likely to cultivate commercial and economically valuable crops. This difference substantially contributes to the gender resource gap since these crops generate a higher market value than traditional staple crops. Moreover, a significantly lower proportion of female holders reported ownership of livestock, especially oxen and equines, which are the primary sources of draught power for plowing and transportation in rural Ethiopia. Overall, this report identifies significant differences in the patterns of agricultural production of male and female holders in Ethiopia and calls for closing these gender gaps, becasue it would yield enormous benefits at the individual, household, and national levels. The report also puts forward policy priorities for prospective interventions.